A PZT-assisted single particle loading method for dual-fiber optical trap in air. (June 2020) - Xiao, Guangzong; Kuang, Tengfang; Xiong, Wei; Han, Xiang; Luo, Hui
Highlights: Benefit for the engineering applications of optical trapping in air. Controllably load particle to optical trap in air within a short distance. Launch particle with both high driving force and low detachment velocity. Propose the theory about the optimal capturable detachment velocity region. Discuss the effect of different factors to the detachment velocity threshold. Abstract: Efficiently loading particle into optical trap in air is always a challenge, especially for the small enclosed trapping chamber. We propose and demonstrate a novel particle-loading method by optimally selecting the vibration mode of the PZT system. The forces exerted on the particle and its dynamic characteristics in the loading process are investigated. The minimum detachment velocity and the optimal capturable detachment velocity ranges are defined and discussed. We point out that the optimal vibration mode should be selected to ensure that the minimum detachment velocity is tiny lower than minimum capturable detachment velocity. Then the detachment velocity can be enhanced into the optimal capturable detachment velocity range through changing the actuating voltage for the selected vibration mode. Our experiment prove that the method can achieve controllable and highly efficient particle loading into the optical trap in air.